PENGEMBANGAN MODEL PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK DENGAN PENDEKATAN PERMAINAN HALRING PADA SISWA SEKOLAH DASAR (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to produce a model for the development of learning long jump squat style approach halring game in the fourth grade students of SD Negeri 01 Gununglangit District of Kalibening , Banjarnegara regency.This study is a research method development . The procedures include requirements analysis of product development , product manufacture beginning , the first product revision , field trials , the revised final results , product testing , design testing , expert evaluation , small group testing , the first product revision , field trials , test subjects try , data types and data collection instruments . The data was collected using field observation and questionnaires were obtained from expert evaluation and the results of the questionnaire by the students . The data analysis technique used is descriptive percentages .The results obtained by learning experts average percentage analysis results of 95.33 % with a product very well . The results of the student questionnaire data on a small test group gained an average of 88.05 percentage answer with , % with category B. And questionnaire data from a large group of students test answers obtained with the percentage 84.50 % with category B. Based on the research data , it was concluded that the game Halring effectively and in accordance with the characteristics of students that can be used in learning Penjasorkes .